2012
DOI: 10.1111/j.1460-2695.2012.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Triphasic ratcheting strain prediction of materials over stress cycles

Abstract: A B S T R A C T This study intends to formulate ratcheting strain evolution in steel alloys of 42CrMo, 20CS, SA333 Gr. 6 C-Mn and OFHC copper over uniaxial stress cycles. Stages of ratcheting deformation were related to stress cycles, lifespan, mechanical properties and amplitude and mean stress components by means of linear and nonlinear functions. Terms of mechanical properties in the ratcheting formulation enabled to characterize ratcheting response of various materials over life cycles. These terms were fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
(50 reference statements)
0
33
0
Order By: Relevance
“…18 The stages of ratcheting deformation over stress cycles are schematically presented in Fig. 18 The stages of ratcheting deformation over stress cycles are schematically presented in Fig.…”
Section: Parametric Triphasic Ratcheting Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The stages of ratcheting deformation over stress cycles are schematically presented in Fig. 18 The stages of ratcheting deformation over stress cycles are schematically presented in Fig.…”
Section: Parametric Triphasic Ratcheting Equationmentioning
confidence: 99%
“…Bower 10,11 has modified Armstrong-Frederick (A-F) model 6 by introducing the second kinematic variable to decrease the A-F constant ratcheting strain rate as the number of stress cycles advanced. 18 In this study, ratcheting response of four steel alloys will be examined and discussed based on a recently developed parametric equation and the hardening rule of Bower. 1,2,[12][13][14][15][16] Ratcheting deformation is attributed to plastic slip, dislocation movement and cell formations.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Ratcheting progress over asymmetric stress cycles was found as a result of cyclic plastic strain accumulation in materials extended over distinct stages with various rates and magnitudes. [18][19][20][21][22] Kang et al 24 reported macroscopic evidences of ratchetting deformation over uniaxial loading cycles in 316L stainless steel coinciding with dislocation activities over stress cycles. Microscopic examinations have revealed that progressive deformation over these stages was associated with plastic slip, dislocation interactions, and number of active dislocations.…”
Section: Ratcheting Mechanisms and Stagesmentioning
confidence: 99%
“…Parametric equations have been structured based on the applied mean and amplitude of stresses, cyclic hardening or softening behaviours, and number of cycles. 18,21,184 Analogous to creep phenomenon, the stages of ratcheting as illustrated in Figure 2 expand over life cycles. Experimental evidences have supported triphasic response of ratcheting in engineering alloys.…”
Section: Figure 18mentioning
confidence: 99%
“…2,6 During last stage, ratcheting process is typified as ratcheting strain rate increases uncontrollably in successive cycles resulting in the cross-sectional area reduction. 8 Ratcheting deformation has been intensively discussed for various materials in the literature. 2,4,6,7 The triphasic ratcheting response of materials over stress cycles with positive s m /s a ratios has been formulated in a recent paper by the present authors.…”
Section: Introductionmentioning
confidence: 99%